A diffusion weighted imaging study of basal ganglia in schizophrenia. (2nd January 2018) - Delvecchio, Giuseppe; Pigoni, Alessandro; Perlini, Cinzia; Barillari, Marco; Versace, Amelia; Ruggeri, Mirella; Altamura, A. Carlo; Bellani, Marcella; Brambilla, Paolo
Abstract: Objectives: Several magnetic resonance imaging (MRI) studies provided evidence of selective brain abnormalities in schizophrenia, both in cortical and subcortical structures. Basal ganglia are of particular interest, given not only the high concentration of dopaminergic neurons and receptors, but also for their crucial role in cognitive functions, commonly impaired in schizophrenia. To date, very few studies explored basal ganglia using diffusion imaging, which is sensitive to microstructural organization in brain tissues. The aim of our study is to explore basal ganglia structures with diffusion imaging in a sizeable sample of patients affected by schizophrenia and healthy controls. Methods: We enrolled 52 subjects affected by schizophrenia according to DMS-IV-R criteria and 46 healthy controls. Diffusion weighted images were obtained using a 1.5 Tesla scanner and apparent diffusion coefficient (ADC) values were determined in axial and coronal sections at the level of basal ganglia. Results: Patients affected by schizophrenia showed a significantly higher ADC compared to healthy controls in the left anterior lenticular nucleus ( F = 3.9, p = .05). A significant positive correlation between right anterior lenticular nucleus and psychotropic dosages was found ( r = 0.4, p = .01). Conclusions: Our study provides evidence of lenticular nucleus microstructure alterations in schizophrenia, potentially sustaining cognitive and motor deficits in schizophrenia. Key points: The basal ganglia structures was explored with diffusion imaging in a sizeable sample of patients affected by schizophrenia and healthy controls. Patients affected by schizophrenia showed a significantly higher ADC compared to healthy controls in the left anterior lenticular nucleus. Our study provides evidence of lenticular nucleus microstructure alterations in schizophrenia, potentially sustaining cognitive and motor deficits in schizophrenia.